Efeito do cálcio sobre as características anátomicas de raízes de milho (Zea mays L.) ¨Saracura¨ BRS-4154 submetido ao alagamento em casa de vegetacao (2004)
Saracura” BRS-4154 maize is an alternative for the areas subject to temporary flooding. Researches have been demonstrating that CaCl2 presence in flooded germination atmosphere increases “Saracura” maize tolerance to that condition. This work was conducted in greenhouse at Embrapa Milho e Sorgo, located in Sete Lagoas – MG, with the objective of obtaining better knowledge of anatomical alterations in “Saracura” BRS-4154 maize under the effect of calcium and flooding. Plants were submitted to treatments with and without addition of 300 kg ha-1 calcium chloride, incorporated in the whole soil. Each treatment was evaluated under regular irrigation conditions and under flooding imposed from stage V6 until flowering; the control treatment had normal irrigation and no calcium application. Assay evaluations were accomplished during flowering. Five to eight cm detached roots fragments were submitted to classic micro techniques to make and analyze tissues. Anatomical differences were observed among treatments - flooded and with normal irrigation - in relation to epidermis thickness, thicker in normal conditions. The aerenchyma presence only occurred in plants in flooded conditions, proving that those are not constituent of this species. The aerenchyma proportion decreased with calcium application, showing the participation of this ion in cell wall structure, avoiding disordered collapse and increasing the survival of the plant in flooded conditions. Calcium application influenced cellular epidermis arrangement and promoted a smaller exoderm thickness in normal irrigation conditions.